Studi Etnometodologi Islam: Mengupas Praktik Akuntansi berbasis Nilai Budaya Lokal - Mohamad Anwar Thalib; Anisa Nurhayati Sujianto; Hilwa Faradhilla Sugeha; Sindriyanti Huruji (LPPM UBP, 2023)
This study aims to reveal accounting practices in implementing iftar at the mosque. This study uses an Islamic paradigm with an Islamic ethnomethodology approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and ihsan. The results of the study show that first, the costs for breaking the fast are borne by 3 to 5 heads of households; second, the amount of cost to buy heavy consumption is adjusted to the ability of the group who is willing to give iftar; the third is infaq costs that are voluntary. The practice of cost accounting in organizing iftar at the mosque is conditional on the value of togetherness, whose ultimate goal is to expect ridho from the Creator. In the Islamic culture of Gorontalo, the elders often advise these values through lumadu (advice)